Hubungan Indeks Masa Tubuh (IMT) dengan Kadar Kolesterol Total pada Komunitas Masyarakat di Kota Malang - Susilowati, Endang; Susanti, Erna (LPPM-KI - POLTEKKES PIM (Formerly AKAFARMA-AKFAR PIM, 2025)
Obesity is a health problem in many countries, both developed and developing, including Indonesia. The increasing trend indicates that obesity in Indonesia remains a serious public health issue. This study aimed to determine the relationship between BMI and total cholesterol levels in the community of Malang City, which may serve as a basis for policymaking in community-based non-communicable disease prevention programs. The study was conducted using a cross-sectional design on 30 respondents, selected through purposive random sampling. The results of the bivariate analysis showed a p-value < 0.05, indicating a significant relationship between BMI and total cholesterol levels. The correlation coefficient (ρ) was 0.738, suggesting a strong positive correlation between the two variables. This means that the higher a person’s BMI, the higher their total cholesterol levels tend to be in this population. In conclusion, this study demonstrates a significant and strong relationship between BMI and total cholesterol levels in the studied community. These findings support the hypothesis that excess body weight contributes to increased cholesterol levels and may serve as a basis for preventive and promotive interventions in the community.